2017
DOI: 10.1101/226472
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

TheVibrio choleraeType VI Secretion System Can Modulate Host Intestinal Mechanics to Displace Commensal Gut Bacteria

Abstract: Host-associated microbiota help defend against bacterial pathogens; the mechanisms that pathogens possess to overcome this defense, however, remain largely unknown. We developed a zebrafish model and used live imaging to directly study how the human pathogen Vibrio cholerae invades the intestine. The gut microbiota of fish mono-colonized by commensal strain Aeromonas veronii was displaced by V. cholerae expressing its Type VI Secretion System (T6SS), a syringe-like apparatus that deploys effector proteins into… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Using genetic approaches to interrogate regulation of the T6SS in V. fischeri, we have found that the T6SS is positively regulated by 54 and the bEBP VasH during symbiosis. The role and prevalence of the T6SS in beneficial bacteria is an emerging field of study that is revealing the impact of the T6SS weapon on microbiota composition and assembly (12,42,43). A current obstacle to understanding how the T6SS affects the assembly of symbiont populations within a host ecosystem has been the inability to study the factors that regulate these nanomachines during symbiosis establishment.…”
Section: Discussionmentioning
confidence: 99%
“…Using genetic approaches to interrogate regulation of the T6SS in V. fischeri, we have found that the T6SS is positively regulated by 54 and the bEBP VasH during symbiosis. The role and prevalence of the T6SS in beneficial bacteria is an emerging field of study that is revealing the impact of the T6SS weapon on microbiota composition and assembly (12,42,43). A current obstacle to understanding how the T6SS affects the assembly of symbiont populations within a host ecosystem has been the inability to study the factors that regulate these nanomachines during symbiosis establishment.…”
Section: Discussionmentioning
confidence: 99%
“…The T6SS yielded by bacterial pathogens targeting host cells presents a further risk to the microbiota, since the ensuing subversion of host processes affects their ecological niche. Indeed, such indirect impact has been demonstrated in the zebrafish model of cholera, where the actin-crosslinking domain of VgrG1 of V. cholerae stimulates peristalsis, resulting in the collapse of the resident microbial community (Logan et al, 2018). The gradual repopulation by the commensal microbiota may evict the invading pathogen despite the reversal of the numerical advantage; yet the niche must still be conducive for this repopulation to occur.…”
Section: Direct Host Cell Contact: T6ss Encounters Of the Third Kindmentioning
confidence: 99%
“…To study the basic principles of how microbes interact with one another and the host, Parthasarathy's team populates a sterile zebrafish gut with only a couple species. For example, in a study published earlier this year, they showed how the cholera virus might infect its host (8). After colonizing an otherwise sterile zebrafish gut with a bacterium called Aeromonas veronii, the researchers introduced the cholera virus, discovering that the virus induces the gut to contract, which expels the bacterium and enables the virus to take over.…”
Section: Microbiomes At the Moviesmentioning
confidence: 99%